Three new Zodarion species (Araneae: Zodariidae) from Southeastern Turkey - Coşar, Ilhan; Danişman, Tarik (Zootaxa, 2021)
Three new species of zodariid spiders are described from Turkey: Zodarion ozkutuki spec. nov., Zodarion turkesi spec. nov. and Zodarion yagmuri spec. nov. New photographs of genitalia are provided for Zodarion van Bosmans 2009.